Gambaran Faktor Risiko Kejadian Gagal Ginjal Kronik - Putri, Yolanda Eka; Suryarinilsih, Yosi; Anggraini, Sila Dewi; Efitra, Efitra; Bahar, Idrawati; Delima, Delima; Renidayati, Renidayati (Poltekkes Kemenkes Padang, 2025)
Chronic kidney failure is a condition characterized by the inability of the kidneys to maintain metabolism and fluid-electrolyte balance due to progressive structural damage, resulting in the accumulation of metabolic waste. Interviews with patients revealed that the main risk factors include hypertension, diabetes mellitus, and unhealthy lifestyles. Alarmingly, even young patients (aged 19 and 24 years) have experienced this condition. This study aims to describe the risk factors associated with chronic kidney failure using a descriptive research design. Out of a population of 90 individuals, 73 respondents participated. Data were collected through questionnaires and analyzed using univariate analysis. The study was conducted from September 2023 to June 2024 in the Hemodialysis Unit of Dr. Reksodiwiryo Level III Hospital, Padang. The results showed that most respondents were aged 46–65 years (68.5%), female (56.2%), had a history of hypertension (76.7%), diabetes mellitus (61.6%), and long-term medication use (68.5%). A smaller proportion were smokers (24.7%) and had other medical histories. In conclusion, the main risk factors for chronic kidney failure are hypertension, diabetes, and long-term medication use. It is recommended to improve public education and awareness about healthy lifestyles to prevent chronic kidney failure from an early age.